User acceptance of mobile notifications - Westermann, Tilo (Springer, 2017)
This book presents an alternative approach to studying smartphone-app user notifications. It starts with insights into user acceptance of mobile notifications in order to provide tools to support users in managing these. It extends previous research by investigating factors that influence users' perception of notifications and proposes tools addressing the shortcomings of current systems. It presents a technical framework and testbed as an approach for evaluating the usage of mobile applications and notifications, and then discusses a series of studies based on this framework that investigate factors influencing users' perceptions of mobile notifications. Lastly, a set of design guidelines for the usage of mobile notifications is derived that can be employed to support users in handling notifications on smartphones.
Keywords: Mobile apps.; Mobile computing.; Application software.; elektronické knihy; electronic books